Implementation of Fishbone Analysis in Managing Warehousing Problems at PT Sari Warna Asli V Kudus - Muhammad Navis Mirza; Iwan Prasetyo; Viki Shopiyan (Yayasan Adra Karima Hubbi, 2024)
Background. Warehouse management is crucial for manufacturing companies to ensure production runs smoothly and demand is met efficiently. Poor warehouse management can lead to several issues, such as dirty and dusty conditions, inconsistent goods recording, and suboptimal spare parts layouts. These problems can hinder operational efficiency and disrupt production. Purpuse. This research aims to address inefficiencies in the spare parts warehouse management at PT Sari Warna Asli V Kudus. Specifically, the study seeks to identify the root causes of these issues using fishbone analysis and propose practical solutions to improve the warehouse's operational efficiency. Method. The study was conducted as part of a student internship from February to April 2024 at PT Sari Warna Asli V Kudus. It involved a preliminary review, problem identification, data collection from primary and secondary sources, and the application of fishbone analysis. The process included gathering data, creating a causal factor diagram, identifying the root causes, and recommending solutions. Results. The research found that the main problems in the warehouse included the lack of a Standard Operating Procedure (SOP) for managing warehouse activities such as receiving and sending goods, cleanliness, regular inspections, and stock management. These gaps contributed to the inefficiencies in the warehouse operations. Conclusion. To improve warehouse management at PT Sari Warna Asli V Kudus, the study recommends the implementation of consistent SOPs, regular inspections, and monthly stocktaking. Additionally, warehouse staff should receive training to enhance their skills and knowledge. These measures are expected to significantly improve warehouse conditions and overall operational efficiency.